THE RELATIONSHIP AMONG SAVINGS, INFLATION AND LOANS AT COMMERCIAL BANK IN WEST KALIMANTAN: VECTOR AUTO REGRESSION APPROACH - B01111063, DEDDI (Jurnal Pembangunan dan Pemerataan, 2016)
The title of this research is "The Relationship among Savings, Inflation and Loans at Commercial Bank in West Kalimantan: Vector Auto Regression Approach". This study is aimed to examine the causality, shocks and trends and to test the most potential dependent variables among savings, inflation and loans at commercial bank in West Kalimantan. The study used quarterly data with 48 observations. This study uses a vector auto regression approach.The analysis showed that there is does not have bi-directional causality among savings, inflation and loan. The results of Impulse Response Function shows that the savings and loan itself provides a positive shock while inflation is likely to provide negative shocks to loan. Credit itself along with two other variables that mostly provide negative shocks on inflation and most provide a positive shock to the savings.Variance decomposition results showed that the most potential dependent variables is loan and the most potential independent variables is the savings and inflation.Keywords: savings, inflation, lending, vector auto regression